Inhibition of pathogenic bacterial carbonic anhydrases by monothiocarbamates - Simone Giovannuzzi; Anil Kumar Marapaka; Nader S. Abutaleb; Fabrizio Carta; Hsin-Wen Liang; Alessio Nocentini; Luigi Pisano; Mohamed N. Seleem; Daniel P. Flaherty; Claudiu T. Supuran (Taylor & Francis Group, 2023)
Carbonic anhydrases (CAs) from the pathogenic bacteria Nesseria gonorrhoeae and vancomycin-resistant enterococci (VRE) have recently been validated as antibacterial drug targets. Here we explored the inhibition of the α-CA from N. gonorrhoeae (α-NgCA), of α- and γ-class enzymes from Enterococcus faecium (α-EfCA and γ-EfCA) with a panel of aliphatic, heterocyclic and aryl-alkyl primary/secondary monothiocarbamates (MTCs). α-NgCA was inhibited in vitro with KIs ranging from 0.367 to 0.919 µM. The compounds inhibited the α-EfCA and γ-EfCA with KI ranges of 0.195-0.959 µM and of 0.149-1.90 µM, respectively. Some MTCs were also investigated for their inhibitory effects on the growth of clinically-relevant N. gonorrhoeae and VRE strains. No inhibitory effects on the growth of VRE were noted for all MTCs, whereas one compound (13) inhibited the growth N. gonorrhoeae strains at concentrations ranging from 16 to 64 µg/mL. This suggests that compound 13 may be a potential antibacterial agent against N. gonorrhoeae.